Penggunaan Media Sosial Instagram Haloa Cafe sebagai Komunikasi Pemasaran Online - Rizky, Nurul; Dewi Setiawati, Sri (Jurnal Ilmu Komunikasi, 2020)
The rapid development of business today has resulted in increasingly fierce competition. Not only how a business provides products and services but how the products and services that have been produced can be accepted, known, by consumers. Marketing communications today can be done anywhere and anytime due to technological advances such as social media. In this study the researcher aimed to find out how the Haloa Cafe's marketing strategy through social media Instagram, in this study using the new media theory. The method used is a case study with a qualitative approach. The result of this research is that Haloa Cafe chooses social media Instagram as the main marketing tool in social media. This is attributed to the increasing number of Instagram social media users and in accordance with the marketing target of Haloa Café.